(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
According to the first story of Hazrat Alisher Navoi’s work "Khamsatul-mutahayirin", Abdullah brings the scribe Khoja Abdullah Ansari’s treatise "Ilohiynama" to Alisher Navoi. The author of the treatise, whose full name is Abu Ismail Abdullah bin Abiy Mansur Muhammad al-Ansari, had a very strong memory, according to the testimony of sources. Commentary on the Qur’an had been finished. He created dozens of works such as "Naqli Tabaqati Sufiya", "Koshiful-asrar", "Munojotnama", "Muhabbatnama", "Zad ul-arifin", "Kand ul-Salikin", "Qalandarnama", "Haft hisar".